RIPK3 inhibitor GSK872 targets angiotensin II induced cardiomyocyte hypertrophy by regulating Ca2+/ calmodulin dependent protein kinase II - Jingjing Zhang; Huijie Yu; Yuxin Yang; Ajie Liu; Peng Wang (PLoS ONE, 2026)
Receptor interacting protein kinase 3 (RIPK3) plays a crucial role in the signaling pathway of necrotic apoptosis, and calcium/calmodulin dependent protein kinase II (CaMKII) is a novel substrate for RIPK3 induced regulated necrosis. The aim of this study is to investigate the regulation and mechanism of RIPK3 on AngII induced cardiomyocyte hypertrophy. Using AngII to stimulate myocardial cells for 72 hours, inducing myocardial cell hypertrophy; Intervention of RIPK3 expression using RIPK3 inhibitor GSK872. Detect indicators related to myocardial hypertrophy, cell damage, regulatory necrosis, CaMKII activation and gene expression, oxidative stress, mitochondrial membrane potential, etc. After AngII stimulation of cardiomyocytes, the expression of hypertrophy markers ANP and BNP increased, LDH release increased, ATP levels decreased, splicing factors ASF and SC35 expression increased, CaMKII oxidation and phosphorylation levels increased, and CaMKIIδ alternative splicing was disrupted. However, treatment with GSK872 can alleviate myocardial dysfunction, inhibit CaMKII activation, correct CaMKIIδ variant splicing disorder and ultimately alleviating myocardial hypertrophy. In addition, pretreatment with RIPK3 can reduce the accumulation of reactive oxygen species (ROS) induced by AngII, decrease the activity of ASF and SC35, and restore mitochondrial membrane potential. RIPK3 inhibitor GSK872 can inhibit the activation of CaMKII, alleviate regulated necrosis and oxidative stress to alleviate myocardial hypertrophy. It has a protective effect on myocardial hypertrophy and is expected to become a new targeted drug for clinical treatment of dilated cardiomyopathy and heart failure.